SENSIBILITAS MULTIMEDIA DAN KETERKAITANNYA DENGAN KESULITAN DALAM PEMBELAJARAN BAHASA JEPANG - Dwiwardani, Wury; Wardhani, Devi (IZUMI, 2017)
(Title: Multimedia Sensibility And Its Relation With Difficulties In Japanese Language Learning) The development of technology and the popularity of multimedia as a means of conveying information have conditioned society to change into a multimedia community with unique characteristics, sensibility, and needs. This study aims to see the effect of multimedia sensibility on the difficulties in the process of learning Japanese. Data were taken from a survey conducted on the students and analyzed using concepts related to the characteristics of the multimedia society. The results of this study show that multimedia sensibility has an effect on student’s difficulties in understanding learning materials delivered using different media. The new needs of the multimedia society have to be answered with various adjustments. However, by only paying attention to the multimedia sensibility and needs, there is a possibility that learning activities become less reliable in sharpening analytical skills. Therefore, choosing the right materials and methods is important so that the learner’s interest can be sustained by adjusting to their needs and sensibility, and also considering activities that can sharpen other abilities, such as analytical skills, which is very important for student self- development. gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor